Pathological findings in a patient with non-dystrophic myotonia with a mutation of the SCN4A gene; a case report - Hata, Takanori (BMC Neurol, 2019)
BACKGROUND: Non-dystrophic myotonias (NDMs) are skeletal muscle disorders involving myotonia distinct from myotonic dystrophy. It has been reported that the muscle pathology is usually normal or comprises mild myopathic changes in NDMs. We describe various pathological findings mimicking those of myotonic dystrophy (DM) in biopsied muscle specimens from a patient with NDMs with a long disease duration. CASE PRESENTATION: A 66-year-old Japanease man presented eye closure myotonia, percussion myotonia and grip myotonia together with the warm-up phenomenon and cold aggravation from early childhood. On genetic analysis, a heterozygous mutation of the SCN4A gene (c.2065 C > T, p.L689F), with no mutation of the CLCN1, DMPK, or ZNF9/CNBP gene, was detected. He was diagnosed as having NDMs. A biopsy of the biceps brachii muscle showed increasing fiber size variation, internal nuclei, chained nuclei, necrotic fibers, fiber splitting, endomysial fibrosis, pyknotic nuclear clumps and disorganized intermyofibrillar networks. Sarcoplasmic masses, tubular aggregates and ragged-red fibers were absent. CONCLUSION: It is noteworthy that the present study revealed various pathological findings resembling those seen in DM, although the pathology is usually normal or mild in NDMs. The pathological similarities may be due to muscular modification with long-standing myotonia or excessive muscle contraction based on abnormal channel activity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12883-019-1360-0) contains supplementary material, which is available to authorized users.